Trade agreements and related treaties and conventions in Canada. - Hii, Minna Wei Jye. (2008)
This research paper will explore each of the three trade agreements in the areas of trade liberalisation, trends, developments, impacts on businesses and trade, limitations and future directions. Canada's trade is not limited to trade agreements alone. This paper also explores the current tax treaties Canada has signed with other nations and its withholding rates.